Factors contributing to the development of sarcopenia in patients with liver cirrhosis: An integrative review (Research, Society and Development, 2024)
Sarcopenia is a condition marked by the loss of muscle mass and function, which can occur primarily due to aging or secondarily due to diseases like liver cirrhosis. Cirrhosis is a chronic illness that damages liver cells and impairs liver function. This integrative review seeks to identify the factors that contribute to the development of sarcopenia in patients with cirrhosis by analyzing and synthesizing findings from existing studies on the topic. Data were collected from PubMed and SciELO, with six articles meeting the eligibility criteria. The studies suggest that various factors may contribute to sarcopenia in cirrhotic patients, including hypermetabolism, increased catabolism, low testosterone levels, reduced branched-chain amino acids, and low zinc levels.